2013
DOI: 10.1080/00222348.2012.742823
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Carbon Nanotube Networking on the Conductive, Crystallization, and Thermal Expansion Behaviors of PA610-Based Nanocomposites

Abstract: The electrical, crystallization and thermal expansion behaviors of polyamide 610 (PA610)/multi-walled carbon nanotube (CNT) nanocomposites prepared by melt mixing were investigated. Electron microscopy (Scanning Electron Microscopy and Transmission Electron Microscopy) revealed that a good dispersion of CNT and CNT networkwas obtained in the PA610 matrix. Addition of CNT to PA610 matrix led to polymer nanocomposites exhibiting higher electrical conductivity and lower thermal expansion. The network of CNT in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…Studies have shown that the minor melting peak corresponds to the formation of γ‐form crystalline structures while the major peak corresponds to the α‐form crystalline structure . The γ‐form crystalline phase is considered an imperfect crystal formation with hydrogen bonding formed between parallel chains while the α‐form crystalline phase is more stable with hydrogen bonds formed between anti‐parallel chains which is less stretched in the rotation of the chains and, therefore, increasing the packing of the chains (crystallinity) . This double melting peak phenomenon in PA has been described in literature as the perfection of crystals during melting where poor crystal formation improves during melting to a more perfect crystal formation .…”
Section: Resultsmentioning
confidence: 97%
“…Studies have shown that the minor melting peak corresponds to the formation of γ‐form crystalline structures while the major peak corresponds to the α‐form crystalline structure . The γ‐form crystalline phase is considered an imperfect crystal formation with hydrogen bonding formed between parallel chains while the α‐form crystalline phase is more stable with hydrogen bonds formed between anti‐parallel chains which is less stretched in the rotation of the chains and, therefore, increasing the packing of the chains (crystallinity) . This double melting peak phenomenon in PA has been described in literature as the perfection of crystals during melting where poor crystal formation improves during melting to a more perfect crystal formation .…”
Section: Resultsmentioning
confidence: 97%
“…23,24 The g-form crystalline phase is considered an imperfect crystal formation with hydrogen bonding formed between parallel chains while the aform crystalline phase is more stable with hydrogen bonds formed in-between anti-parallel chains which increases the packing of the chains (crystallinity). 25 This double melting peak phenomenon has been described in literature as the perfection of crystals during melting where poor crystal formation improves during melting to a more perfect crystal formation. 26 It should also be noted that the smaller peak in NB is marginally more pronounced than that of the neat nylon.…”
Section: Thermal Analysismentioning
confidence: 95%
“…In the extensive literature on PA/CNT NCs, PA6 is the commercial polyamide most frequently used in the production of this type of nanocomposite [8][9][10]. However, other PAs, such as PA66 [11,12], PA12 [13], PA610 [14], PA1010 [15], and PA11 [16], and to a lesser extent PA46 [17] and PA1212 [18], have also been studied. It is worth mentioning that articles on bio-based PAs are rare [5,19,20] and studies on bio-PA/CNT NCs are practically non-existent.…”
Section: Introductionmentioning
confidence: 99%